EP.FRI.479 Clinical accuracy of u/sound combined with inflammatory markers in Acute Appendicitis. (28th October 2021) - Gulnaz, Nadia; Tasleem, Sadia; Abdullah, Farooq
Abstract: : Traditionally acute appendicitis has been a clinical diagnosis based on patients' history and physical examination, but the accuracy of clinical diagnosis ranges from 70-95%. Pre-operative diagnosis of acute appendicitis still remains an enigmatic challenge, because no single test alone can reduce the rate of negative appendectomy. Hence some authors have recommended a combination of two or more investigations to increase accuracy and therefore the use of imaging is gaining support. The objective of the study was to determine the clinical accuracy of ultrasound, combined with inflammatory markers such as CRP, WBC, and neutrophilia keeping histopathology as the gold standard. Methods: The study was conducted in a Tertiary care hospital in Peshawar from September 2014 to March 2015 on 250 patients who were clinically diagnosed with acute appendicitis. All these patients underwent u/sound scanning in addition to blood tests. Findings: In this study, WBC had the highest sensitivity (77.68%) followed by neutrophil% (69.96%), CRP(67.10%), and U/Sound (62.96%) respectively. While U/Sound had the highest specificity (70.59%) followed by CRP and TLC (64.71% each) and neutrophil% (58.82%) respectively. When all the four tests were combined the sensitivity, specificity, (99.17% and 98.45%) increased significantly. When all four tests were negative, appendicitis could be safely ruled out. Conclusion: Acute appendicitis is very unlikely and surgery can be safely deferred in these patients when all tests are negative thereby reducing the negative appendicectomy rates.